Fiestas agrícolas y ciclos helio-lunares en el mundo andino: el carnaval como fuente de justicia de los pueblos indígenas pastos y kamentsás (2009)
The article presents the most prominent aspects in the carnivals of Inti Raymy and forgiveness, being read under the light of the relation between time, language and justice. The first part of the text limits an analysis framework to think the carnival as an ethical regulation space meanwhile the second part tests the importance of reading through the voices of comuneros who participate in the carnival. It is about an ethnographical work that tries to make evident the social ruling that underlies this type of celebrations.